Doppler and Contrast‐Enhanced Ultrasonography of Testicles in Adult Domestic Felines. Issue 5 (12th June 2015) - de Brito, MBS; Feliciano, MAR; Coutinho, LN; Uscategui, RR; Simões, APR; Maronezi, MC; de Almeida, VT; Crivelaro, RM; Gasser, B; Pavan, L; Russiano, WR
Contents: The objective was to characterize the vascular patterns of testicular blood flow of adult cats, measuring the systolic velocity (SV), diastolic velocity (DV), resistance index (RI), gate time (wash‐in) peak enhancement and output time (wash‐out) of the contrast and addition of tissue fill characteristics. Forty‐five adult cats were selected, and the echotexture, echogenicity, size, contours and margins of testicles were assessed via ultrasound. By Doppler were evaluated the blood flow and determined of vascular index in testicular artery (SV, DV and RI) and via contrast‐enhanced ultrasonography determine the time for phases: wash‐in, wash‐out and peak enhancement. Sonographic findings presented normal. Testicular artery was observed in the spermatic cord with tortuous patter and showed monophasic‐patterned waves and low vascular resistance and with systolic peak evident. Values of indices vascular were as follows: SV = 6.73 cm/s, DV = 2.8 cm/s and RI = 0.54 for left testicles; and SV = 6.23 cm/s, DV = 2.77 cm/s and RI = 0.53 for right testicles. Contrast filled the subcapsular vascular structures and after a few seconds, a homogeneous moderate enhancement of the parenchyma, with parenchymal vessels still distinguishable and after the peak phase, a rapid homogeneous decrease in echogenicity. Values of time for contrast‐enhanced ultrasonography were as follows: wash‐in = 8.78 s, peak enhancement = 21.62 s and wash‐out = 75.36 for left testicles; and wash‐in = 10.76 s, peak enhancement = 21.50 s and wash‐out = 81.81 for right testicles. Doppler and contrast‐enhanced ultrasonography of the testicles in healthy adult cats was easily implemented and may provide baseline data for this organ to allow the use of these techniques as a diagnostic tool for evaluating testicular abnormalities in sick cats.